"I'll Show You the Bowery from Chatham Square to the Cooper Institute": The Entertainment and Ethics of Slumming in the Theatre. Issue 2 (1st May 2015) - Westgate, J. Chris
Abstract : In 1894, Robert Neilson Stephens's play On the Bowery debuted at Haverly's Fourteenth Street Theatre in New York City, with Steve Brodie, who had won fame for purportedly jumping from the Brooklyn Bridge years earlier, playing himself. Although Brodie's entrance is delayed until the second act, he rather quickly commandeers the plot and leads the rest of the characters through the Bowery and across the Brooklyn Bridge (where he reenacts his jump to enthusiastic audiences) to an East River pier, where he leaps into a burning building to rescue one of those perpetually distressed damsels from the 1890s. Naturally, mainstream newspapers were rather critical of On the Bowery 's literary merits. The New York Herald claimed that the play made "no dramatic pretensions, " and the Philadelphia Inquirer emphasized that it left the critic not "overly impressed with the play as a play." The New York Times took an especially harsh line. Lamenting the play's "threadbare plot" and "no originality, " and overreliance on Brodie's celebrity, its critic used the production as an opportunity to advance rigid delineations of highbrow and lowbrow, upper class and lower class, and literature and leisure. For what this reviewer described as the "Brodie audience, " the working-class spectators who crowded the gallery and boisterously cheered Brodie's every feat, On the Bowery gratified a yearning for escapism and entertainment. On the Bowery was not, according to the Times, geared to what the reviewer described as the "Booth audience, " the middle- and upper-class spectators who normally prized Edwin Booth's Shakespearean performances: "even the management does not take [Brodie] seriously." If box office success is any measure, however, many from both the Booth and Brodie audiences did take On the Bowery seriously. Productions of the play toured for nearly three years, and a number of plays emulated On the Bowery during the next five years. If Bruce McConachie is right that what is relevant is not "whether . . . melodramas were any good" but what audiences were watching and what meanings they were constructing from these plays, then theatre history should take On the Bowery seriously too.